2006
DOI: 10.1021/la061138j
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-Controlled Reaction Sites in Biocatalytic Films for Electrochemical Reduction of Vicinal Dibromides

Abstract: We report herein the electrochemical dehalogenation of vicinal dibromides in microemulsions using cross-linked films of the redox protein myoglobin (Mb) and poly-l-lysine (PLL) covalently bonded to carbon electrodes. Catalytic reduction of the dibromides to olefins was more efficient in an SDS microemulsion than in a CTAB microemulsion. SDS shifts the Mb redox potential more negative, but a comparison to Mb-SDS films suggests that the activation free energy of the reduction is controlled by an inner-sphere mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We used our previously reported method to construct cross-linked protein-PLL films (see Supporting Information for full details). , This involved initial covalent linkage of a layer of PLL (MW 150−300) onto electrochemically oxidized pyrolytic graphite electrodes, aminosilyl fused silica slides with poly(acrylic acid) attached, or carboxylated 0.5 μm diameter silica beads. A layer of PLL was first attached to the carboxylated surfaces by amide linkages promoted by using freshly prepared 24 mM 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide (EDC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used our previously reported method to construct cross-linked protein-PLL films (see Supporting Information for full details). , This involved initial covalent linkage of a layer of PLL (MW 150−300) onto electrochemically oxidized pyrolytic graphite electrodes, aminosilyl fused silica slides with poly(acrylic acid) attached, or carboxylated 0.5 μm diameter silica beads. A layer of PLL was first attached to the carboxylated surfaces by amide linkages promoted by using freshly prepared 24 mM 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide (EDC).…”
Section: Methodsmentioning
confidence: 99%
“…Quartz crystal microbalance measurements suggested that these 2 bilayer films of enzyme-PLL are 400−600 nm thick . Standard, previously reported procedures were used for voltammetry and spectroscopy. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are useful for biocatalysis because they can dissolve organic reactants in their oil nanophases while keeping the enzymes in LbL films in a largely aqueous environment. [43][44][45] Additional stabilization was required for LbL films to be usable in microemulsions. Excellent stability and catalytic efficiency in buffers and microemulsions at room temperature was obtained for LbL films on electrodes by linking Mb to poly(L-lysine) (PLL) covalently bound to graphite electrodes.…”
Section: Enhancing Stability Of Enzyme Lbl Filmsmentioning
confidence: 99%
“…Ionic liquid-in-oil (IL/O) microemulsion allows chemical reactions that require nonaqueous medium to successfully take place in its core . Some microemulsions also function as bioreactors, where biocatalytic and enzymatic reactions occur selectively in the polar core. , A major limitation of using microemulsion as a drug delivery system is the toxicity resulting from a large amount of surfactants used to stabilize it. This disadvantage can be overcome by using biocompatible surfactants.…”
Section: Introductionmentioning
confidence: 99%